FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN INFORMASI AKUNTANSI PADA UMKM DI KABUPATEN KARAWANG - Robby Johan (Jurnal Akuntansi, 2020)
One of the main factors that cause problems in the activities of micro, small and medium enterprises (MSMEs) in developing their businesses is the lack of ability to use accounting information. The purpose of this study was to determine the effect of recent education, length of effort, business size and accounting knowledge on the use of accounting information. This research is expected to provide benefits for SMEs, the government and subsequent researchers.The population in this study was the number of MSMEs in Karawang Regency. By using a data collection method using a sampling area of ​​100 SME owners with an error rate of 10%. Data is collected by distributing questionnaires to SME owners. Technical analysis uses multiple linear regression analysis.In a partial test the results of the study indicate that accounting knowledge influences the use of accounting information, while the level of education, length of business and scale of business do not affect the use of accounting information. In simultaneous testing the results of the study showed that the level of education, length of effort, scale of business and accounting knowledge together influenced the use of accounting information.